2010
DOI: 10.1371/journal.pgen.1001224
|View full text |Cite
|
Sign up to set email alerts
|

CTCF-Dependent Chromatin Bias Constitutes Transient Epigenetic Memory of the Mother at the H19-Igf2 Imprinting Control Region in Prospermatogonia

Abstract: Genomic imprints—parental allele-specific DNA methylation marks at the differentially methylated regions (DMRs) of imprinted genes—are erased and reestablished in germ cells according to the individual's sex. Imprint establishment at paternally methylated germ line DMRs occurs in fetal male germ cells. In prospermatogonia, the two unmethylated alleles exhibit different rates of de novo methylation at the H19/Igf2 imprinting control region (ICR) depending on parental origin. We investigated the nature of this e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
37
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(40 citation statements)
references
References 74 publications
3
37
0
Order By: Relevance
“…Consequently, the establishment of DNA methylation at hIC1 is inhibited. This finding adds to the growing consensus that H3K4 methylation marks are inhibitory to de novo DNA methylation in the germ line, whereas repressive histone marks do not play major role in the establishment of methylation at ICRs (14,(16)(17)(18)20). However, it is equally possible that the hypomethylated state of DNA attracts H3K4me2 at hIC1 by an unknown mechanism.…”
Section: Resultsmentioning
confidence: 55%
See 1 more Smart Citation
“…Consequently, the establishment of DNA methylation at hIC1 is inhibited. This finding adds to the growing consensus that H3K4 methylation marks are inhibitory to de novo DNA methylation in the germ line, whereas repressive histone marks do not play major role in the establishment of methylation at ICRs (14,(16)(17)(18)20). However, it is equally possible that the hypomethylated state of DNA attracts H3K4me2 at hIC1 by an unknown mechanism.…”
Section: Resultsmentioning
confidence: 55%
“…To investigate factors that may inhibit complete establishment of DNA methylation at hIC1 during spermatogenesis, we examined histone posttranslational modifications at hIC1. Parental allelespecific histone modifications have been described at mIC1 in both somatic and germ cells (14)(15)(16)(17)(18). Several studies have suggested an antagonistic relationship between "activating marks," such as dimethylation and trimethylation of histone H3 at lysine 4 (H3K4me2 and H3K4me3, respectively), and DNA methylation (17)(18)(19)(20).…”
Section: Resultsmentioning
confidence: 99%
“…CTCF has also been shown to block methylation of a bound region (27,28). CTCF binds the Igf2/H19 imprinting control region and acts as a boundary element for the control of imprinted expression of maternal and paternal copies of Igf2 and H19 genes (29,30). Schoenherr et al (27) showed that introducing mutations at the four CTCF-binding sites within the imprinting control region resulted in loss of CTCF binding and a substantial increase in methylation.…”
Section: Model A: Protection From Acquisition Of Methylation Upon Tramentioning
confidence: 99%
“…During mouse spermatogenesis, the paternal-specific methylation pattern is acquired by the maternal H19 allele concomitantly with activation of Boris, and this allele is largely unmethylated while interacting with BORIS [99]. Moreover, in the prospermatogonial stage, both unmethylated H19/Igf2 alleles show different rates of de novo methylation, with the maternal allele presenting a CTCF-dependent delay in gain of methylation [100]. Unlike oocyte chromatin, the haploid nucleosomal chromatin of sperm is repackaged, exchanging histones for small basic protamines, and thus generating highly compact toroidal chromatin essential to sperm function [101,102].…”
Section: Franco Et Almentioning
confidence: 99%